2021
DOI: 10.1111/ejh.13598
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact and risk factors of cancer‐associated thrombosis events in stage‐IV cancer patients treated with immune checkpoint inhibitors

Abstract: Background Cancer‐associated thrombosis (CAT) is a major cause of mortality in cancer patients. Immune checkpoint inhibitors (ICIs) have been associated with multiple side effects including CAT. The aim of this study is to investigate risk factors and prognostic impact associated with CAT events during ICIs treatment. Methods This is a multi‐center retrospective study that included stage IV cancer patients treated with ICIs. Results We identified 552 cancer patients treated with ICIs. During follow‐up time, 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 17 publications
(24 reference statements)
6
52
2
Order By: Relevance
“…The references in the relevant articles were also manually searched for related studies. Overall, 18 retrospective studies reporting incidences and/or outcomes of venous and/or arterial thrombosis in patients on ICIs [ 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and 4 additional relevant systematic reviews and meta-analyses [ 24 , 25 , 26 , 27 ] were identified and included in this review.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The references in the relevant articles were also manually searched for related studies. Overall, 18 retrospective studies reporting incidences and/or outcomes of venous and/or arterial thrombosis in patients on ICIs [ 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and 4 additional relevant systematic reviews and meta-analyses [ 24 , 25 , 26 , 27 ] were identified and included in this review.…”
Section: Methodsmentioning
confidence: 99%
“…The Khorana score was derived in a patient population starting a new line of chemotherapy, and whether it can be applied to patients on ICIs is not fully understood. Most studies that investigated the Khorana score for its prediction performance in patients receiving ICIs have not found it to be predictive [ 11 , 16 , 17 , 18 , 20 ]. This indicates that patients on ICIs likely have different sets of risk factors compared to those on chemotherapy, and a specific risk assessment model in this population may be needed.…”
Section: Prevention Of Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a stage IV tumor is also one of the reasons for the increased risk of TE in cancer patients receiving ICI treatment. In a retrospective cohort study, patients with stage IV tumors had an increased risk of TE ( Kewan et al, 2021 ). Similar results have been reported in the literature indicating that stage IV and/or metastatic disease are closely related to VTE ( Moik et al, 2021 ; Roopkumar et al, 2021 ).…”
Section: Risk Factors For Tementioning
confidence: 99%
“…According to the score, patients are assigned into low-, medium-, and high-risk groups. However, almost all current relevant studies have found that KS is not efficient for identifying cancer patients suitable for VTE prevention ( Nichetti et al, 2019 ; Icht et al, 2021 ; Kewan et al, 2021 ; Moik et al, 2021 ). Only one study has shown that a KS ≥ 1 is significantly associated with VTE ( Sussman et al, 2021 ).…”
Section: Risk Factors For Tementioning
confidence: 99%